The present status of lAS-I sample population - Halder, Shantana R. (BRAC, 2019)
The Research and Evaluation Division (RED) of BRAC recently carried out a quick survey on the present status of the sample population of IAS-I in preparation for the IAS-ll to be conducted during 1996-97. It was contemplated that the sample population of the first study could form a panel for subsequent studies for measuring effective impact of RDP one time by following up the achievements of the respondents. However, this could not be made feasible if there were a significant dropout of members and a similar change in the status of the comparison group through their enrolment in GO/NGO poverty alleviation program. The specific objectives of the study were thus to : (1) determine the present status of both BRAC members and comparison households in terms of their BRAC membership and non- involvement in development programs respectively; (2) ascertain present residential status, (3) find out reasons for dropout of BRAC membership and (4) to identify those sample households which could be considered for preparing a panel of households for the IAS-11.